The Multifaceted Role of Calcium Signaling in Regulated Necrosis - Eric Perez-Rivera; Claudia Plasencia; Uris Ros (Biomolecules)
Calcium is a versatile ion that regulates diverse intracellular processes, including cell death and survival, cytokine and chemokine production, lipid scrambling, and immune cell activation. In regulated necrosis, an early increase in cytosolic calcium is a hallmark of pathways such as pyroptosis, necroptosis, and ferroptosis, and resembles the calcium surge triggered by pore-forming toxins. The complexity of calcium signaling is orchestrated by specialized channels in various cellular compartments and calcium-binding proteins that respond to localized calcium concentrations. However, the coordination of this intricate code during regulated necrosis and its connections to other calcium-driven processes remains poorly understood. This review provides an overview of the molecular mechanisms of calcium signaling in regulated necrosis, analyzing parallels with pore-forming toxin-mediated membrane damage to uncover nodes that are shared by these seemingly independent pathways. We also discuss advanced techniques for studying calcium dynamics, with high precision, that can be applied to study regulated necrosis. Calcium signaling emerges as a central hub where necrotic cell death pathways converge, shaping the unique signatures of dying cells and influencing their communication with the immune system. This integrated perspective highlights the complex and multifaceted role of calcium in cells and its implications for fundamental cellular processes.